(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The simplest and preferred route of drug administration is the oral route. Orodispersible tablets represent a revolution among all routes of drug administration as well as the oral mode of drug administration. Orodispersible drugs are unit dosage forms but have unique properties. It disintegrates in the mouth within a minute for the presence of saliva, where the presence of excellent disintegration in the preparation. New ODT technologies address many pharmaceutical and patient needs ranging from better lifecycle management to convenient dosing for pediatric, geriatric, and psychiatric patients with dysphagia. Orodispersible drug delivery systems are used extensively to improve bioavailability and patient compliance. ODT is an appropriate drug delivery preference in pediatric and geriatric patients as it resolves the problems of dysphagia. The modern article focuses on perfect traits, pros and cons, a range of technologies developed for ODT, evaluation techniques, and current research and future potential.